Education 4.0 in the era of digital transformation: perspectives and possible project concepts - Anna Alexandrovna Paskova (Вестник Майкопского государственного технологического университета)
Digitalization changes the values and spheres of the existing industries. Technological achievements caused by the fourth industrial revolution (Industry 4.0) are developing incredibly fast, changing the image of our life, work and functioning of society as a whole. Artificial intelligence, robotics, Big Data and Internet of things in aggregate affect the labor market and the economy as a whole. Future employees should be well trained not only in new technologies, but, which is equally important, but in values related to the use of these technologies and should have such qualities as creativity, flexibility and adaptability.In order to take full advantage of the opportunities opened by advanced technologies, a similar revolution in education is needed for the successful training of specialists with new necessary competencies. It is these factors that determine the relevance of the research. As a result of the digital evolution, a new educational model Education 4.0 has appeared, which has been developed in response to Industry 4.0. The problem of the research is to disclose actual aspects of the implementation of Education 4.0 approach. For the successful implementation of the new model a clear understanding of the features of Education 4.0 is needed, its main characteristics, in addition, the adaptation of the practice of teaching to the changed requirements is needed. The aim of the research is to study the features of the new approach to learning, Education 4.0, and analyze its main characteristics. The research methods used are analysis, synthesis, induction, abstraction. The research results: approaches to modern education in the light of Industry 4.0 have been considered, the characteristics of Education 4.0 have been analyzed, such as learning personalization, expanding distance learning capabilities, many educational instruments, project training, simple and accurate estimation, availability of analytical data, mentoring, field experience), Possible ways of forming new competencies and skills in the learning process have been proposed. The key findings: for the successful implementation of Education 4.0 approach in terms of Industry 4.0, it is necessary to change the practice of teaching in accordance with the new requirements for the formation of competencies, the article defines the possible ways of forming such skills as global skills, innovation and creativity skills, technological skills and interpersonal communications kills, which are basic ones in Education 4.0.